Developing quantum dot broadband materials for telecommunications and other applications - Roy-Guay, David (University of Ottawa (Canada), 2010)
Recently, InAs/lnP quantum dot lasers operating in the telecommunications wavelength range showed promising properties such as low threshold, high external efficiency, high bandwidth, multiwavelength emission and passive mode-locking. The photoluminescence of quantum dot layers is investigated, in the scope of improving InAs/InP quantum dot lasers performance operating in the telecommunications range. Stacking of layers with GaP underlayer reduces the full width at half maximum of the emission, improving the laser performances to a competitive alternative to quantum well lasers. Polarization photoluminescence of sample edge emission is investigated to aim for the development of a polarization insensitive semiconductor optical amplifier operating at 1.55 mu m. Polarization properties are studied for a stack period between 5 and 30 nm and for single quantum dot layers rapid thermal annealed from 600 to 700°0. Decreasing the period lowers the degree of polarization of side emission from 80 to 40%, suggesting modification of polarization properties by coupling between the layers.
Keywords: Physics, Quantum.; Physics, Condensed Matter.